2021
DOI: 10.17559/tv-20190820115047
|View full text |Cite
|
Sign up to set email alerts
|

Nano MoS2 Application in Turning Process with Minimum Quantity Lubrication Technique (MQL)

Abstract: In this study, nano-sized MoS2 was mixed into coolant and was turned with GGG-70 spheroidal graphite cast iron. Surface roughness and tool wear were analyzed and effects of nano-MoS2 on machinability were investigated. Cutting tests were carried out at 350 m/min cutting speed, 0.2 mm/feed rate and 4 mm cutting depth. Surface roughness (Ra) values and cutting tool wear obtained under dry cutting, conventional cooling, Minimum Quantity Lubrication (MQL) and 3 different nano-MoS2 added MQL conditions were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The results revealed that the dry condition led to acceptable flank wear and roughness, while reductions in energy and machining time were obtained. Sertsoz and Kacal indicated that the SR of the MQL turning cast iron was decreased by 37.0%, as compared to the dry condition [19]. Kang et al explored the vibration amplitudes and frequencies on the SR using simulation [20].…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the dry condition led to acceptable flank wear and roughness, while reductions in energy and machining time were obtained. Sertsoz and Kacal indicated that the SR of the MQL turning cast iron was decreased by 37.0%, as compared to the dry condition [19]. Kang et al explored the vibration amplitudes and frequencies on the SR using simulation [20].…”
Section: Introductionmentioning
confidence: 99%
“…There are concluded benefits of using nanoparticle. Influence of nanoparticle in MQL on surface roughness, in case of highest cutting speed was analyzed by Şafak and Kaçal [24]. In [25], Abbas et al used artificial neural network with Edgeworth-Pareto method for obtaining of optimal parameters in face milling.…”
Section: Introductionmentioning
confidence: 99%